Nel segno di una primordiale femminilità: il sangue e la donna nel dialogo "In famiglia" (TEST Ticontre. Theory Text Translation, 2020)
In the sign of a primordial femininity: blood and woman in dialogue In famiglia Pavese writes in a letter to Bianca Garufi that in the dialogue In famiglia «c’è il solito problema della donna fatale, ma ironizzato» (Lettere 2, 515). Irony of the Dialoghi con Leucò is an intellectualizing means of symbolizing the mythical material, in this case functional to a reflection conducted on the peculiar history of the woman the interlocutors are talking about: the fickle and detached Elena, real woman-myth, object of desire and conflict, of exaltation and contempt, of defense and condemnation.Figure of the titanic irrational, the Tindaride heroin represents a fully artemid and aphroditic femininity, bringing with itself the danger that this connection entails. Linked to the guilt, to the death and the fate of suffering of humanity, the heroine enjoys a fortune that Pavese recovers, exploring the archaic substratum of myth, reinterpreting a complex character through an allusive game which problematizes, with subtle irony, the tragic conflict at the basis of existence itself.Key words:myth, Pavese, blood, woman, Elena.
Keywords: myth, Pavese, blood, woman, Elena.